Bio-nanoparticles : biosynthesis and sustainable biotechnological implications - Singh, Om V. (Hoboken, New Jersey : Wiley Blackwell, 2015)
"Nanoparticles are considered to be the building blocks for nanotechnology and are referred to as the particles having more than one dimension of the order of 100 nm or less. The nanostructured materials are being offered as better built, long lasting, cleaner, safer, and smarter products for use in communications, medicine, transportation, agriculture and other industries. Topics in molecular recognition, biomolecule-nanocrystal conjugates as fluorescence label for biological cells, and DNA-mediated groupings of nanocrystals are widespread, intriguing researchers from both biological and engineering fields. The diversity of nanotechnology covers fields from biology to material science, physics to chemistry, and other fields with variety of specialties. Controlled size, shape, composition, crystallinity, and structure-dependent properties of nanoparticles govern the unique properties of nanotechnology. The controlled biosynthesis of nanoparticles is of high scientific and technological interest as the microorganisms grab target ions from their environment and then turn the metal ions into the element metal through enzymatic mechanism generated through their cellular (Intra/ Extra) activities. The project aims to introduce the basics and advancements made so far in the field of biosynthesis of nanoparticles for graduate students and researchers around the world. The main aims are to (a) introduce the reader to the variety of microorganisms and their ability to synthesize the nanoparticles, (b) provide an overview of the methodologies applied to biosynthesize the variety of nanoparticles of medical and commercial uses, (c) provide a literature review on diversity of microorganisms able to synthesize nanoparticles of different types, (d) to discuss the regulatory mechanisms in microorganism able to synthesize variety of nanoparticles, (e) discuss experimental design problems associated with the controlled biosynthesis of nanoparticles, (f) discuss the stability and toxicity of nanoparticles in varying environment towards their therapeutic implications. The regulations, challenges and implications of biosynthesized nanoparticles for commercial significance will also represent among the main sections of the book. These aims will be organized by invited research/ review articles from renowned researchers exploring biosynthesis of variety of nanoparticles, and differ in length and number of chapters, with the literature review section containing the bulk of the text."--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Nanoparticles; Microbial biotechnology; Nanoparticles; Bacteria -- metabolism; Biotechnology -- methods; Industrial Microbiology -- methods; Nanotechnology -- methods; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Microbial biotechnology; Nanoparticles; Electronic books; Electronic books